Observations and Implications of Diurnal Climatology and Trends in Direct and Diffuse Solar Radiation Over China. Issue 15 (5th August 2022) - Wang, Yawen; Zhang, Jiahua; Trentmann, Jörg; Fiedler, Stephanie; Yang, Su; Sanchez‐Lorenzo, Arturo; Tanaka, Katsumasa; Yuan, Wenping; Wild, Martin
Abstract: Solar radiation received at the Earth's surface ( R s ) is comprised of two components, the direct radiation ( R d ) and the diffuse radiation ( R f ). R d, the direct beam from the sun, is essential for concentrated solar power generation. R f, scattered by atmospheric molecules, aerosols, or cloud droplets, has a fertilization effect on plant photosynthesis. But how R d and R f change diurnally is largely unknown owing to the lack of long‐term measurements. Taking advantage of 22 years of homogeneous hourly surface observations over China, this study documents the climatological means and evolutions in the diurnal cycles of R d and R f since 1993, with an emphasis on their implications for solar power and agricultural production. Over the solar energy resource region, we observe a loss of R d which is relatively large near sunrise and sunset at low solar elevation angles when the sunrays pass through the atmosphere on a longer pathway. However, the concentrated R d energy covering an average 10‐hr period around noon during a day is relatively unaffected. Over the agricultural crop resource region, the large amounts of clouds and aerosols scattering more of the incoming light result in R f taking the main proportion of R s during the whole day. R f resources and their fertilization effect in the main crop region of China further enhances since 1993 over almost all hours of the day. Key Points: The loss of direct radiation over China since 1993 is relatively large at sunrise and sunset with little effect on solar power generation The diffuse component dominates solar radiation normally near sunrise and sunset, but for the whole day over the main sown area of China The diffuse fraction is further enhanced in the main sown area of China over almost all hours of the day since 1993